Institutional Factors and Financial Sector Development : Evidence from Sub-Saharan Africa - Toroyan, Hovhannes (IMF Working Papers; Working Paper, 2009)
The paper assesses the effects of certain institutional factors on financial sector development in Sub- Saharan Africa (SSA). Data Envelopment Analysis (DEA) is applied to determine the extent to which these institutions affect the financial sector, and to suggest which institutions play a more critical role in each country. Results suggest that institutional factors affect financial depth and access to financial services more than asset quality and profitability (measured by nonperforming loans (NPL) and return on equity (ROE). The results also suggest that depth of credit information has the strongest influence on the NPL ratio, and political stability affects access the most. Based on model findings, policy implications on prioritizing institutional reforms to enhance financial sector development are suggested for individual countries and for country groups.